Pengaruh Leverage dan Pertumbuhan Perusahaan Terhadap Profitabilitas - Endang Susilawati; Albert Kurniawan Purnomo (Owner : Riset dan Jurnal Akuntansi, 2023)
T This study aims to determine the effect of leverage and company growth on profitability. The research method used is descriptive method with a quantitative research type. The data used in this research is secondary data of cement manufacturing companies listed on the Indonesia Stock Exchange in 2016 -202, the amount of data is 15. This research was conducted using a purposive sampling method. The analysis technique uses multiple regression models and uses the SPSS program. This research is expected to be able to provide information to investors so that debt is high and low, because if debt increases, the company's condition is not healthy. The results of this study indicate that partially leverage has an effect and company growth has no effect on profitability. Simultaneous testing shows that leverage and company growth affect profitability.